2016
DOI: 10.1109/jstqe.2015.2507363
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Plasmonic Sensors

Abstract: Mechanical flexibility and the advent of scalable, low-cost, and high-throughput fabrication techniques have enabled numerous potential applications for plasmonic sensors. Sensitive and sophisticated biochemical measurements can now be performed through the use of flexible plasmonic sensors integrated into existing medical and industrial devices or sample collection units. More robust sensing schemes and practical techniques must be further investigated to fully realize the potentials of flexible plasmonics as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Among different polymeric substrate, poly (methyl methacrylate) (PMMA), polyethylene terephthalate (PET) and polycarbonate (PC) are commonly used for creating PANTFs. Besides being inexpensive and transparent, these substrates are highly flexible [25]. It was found that depositing thin layers of TiN on PMMA and PET shows similar plasmonic response as that of TiN deposited on SiO 2 /Si [26].…”
Section: Substratesmentioning
confidence: 99%
“…Among different polymeric substrate, poly (methyl methacrylate) (PMMA), polyethylene terephthalate (PET) and polycarbonate (PC) are commonly used for creating PANTFs. Besides being inexpensive and transparent, these substrates are highly flexible [25]. It was found that depositing thin layers of TiN on PMMA and PET shows similar plasmonic response as that of TiN deposited on SiO 2 /Si [26].…”
Section: Substratesmentioning
confidence: 99%
“…Flexible SERS substrates have potential applications in low-cost embedded and integrated sensors for medical, environmental, and industrial markets [131]. These are mechanically flexible, low-cost, reproducible, and sensitive and can be manufactured using various advanced methods [73,95,96,[132][133][134][135][136][137][138][139][140][141] to have large areas.…”
Section: Flexible Structuresmentioning
confidence: 99%
“…Their plasmonic properties can be tuned by changing shape, size, or morphology of nanostructures and also by mechanically bending, stretching, and twisting. Flexible SERS substrates have been fabricated out of paper and polymers [131]. Electrospinning was used to obtain flexible SERS substrates with 10 9 enhancement by assembling AgNPs on poly(vinyl alcohol) [132].…”
Section: Flexible Structuresmentioning
confidence: 99%
“…8,22–32 This recent and exciting trend now extends the applications of plasmonic sensors beyond laboratory settings for use as wearable sensors or as disposable point-of-care sensors, and also permits their integration into existing medical equipment such as intravenous tubes, syringes, blood bags, bandages, or medical garments. 5,30,33–37 …”
mentioning
confidence: 99%
“…Field portability, low-cost, ease-of-use, and network connectivity are all desired features for ensuring widespread adoption of these sensing systems. 33,38,39 Currently, the most common read-out and quantification scheme for LSPR sensors employs a stable, broad-band light source for illumination and a high resolution optical spectrometer for recording the transmission or reflection spectra. 3,6,40–43 Alternatively, a tunable light source and a single photodiode can be used to obtain the same spectral information.…”
mentioning
confidence: 99%